Rhetorical analysis of specific interpretation in law - Adeodato, João Maurício (2024)
This article is based on the premise that rhetoric is an integral part of philosophical thought and can serve as an instrument for legal methodology in its analytical dimension. In this sense, the descriptive reflection of Law (understood as the set of laws, speeches, decisions, interpretation techniques, etc.) is called “rhetorical analysis”, through which the objective is to better “understand” and “explain it”. For the research, we employed the hypothetical-deductive method with a comparative approach and indirect documentation, conducting a literature review and consulting relevant documents and websites. Within this vision, this article proposes to analyze the specific interpretation in Law, based on how it is seen by ontologists of Brazilian dogmatics, seeking to point out its inconsistencies and mistakes from a rhetorical perspective. In the end, we conclude that the specified interpretation mechanism is, despite its typical ontological defects, an excellent rhetorical methodological instrument through which jurists operate legal arguments.